2003
DOI: 10.1128/jvi.77.2.1021-1038.2003
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Ex Vivo Fitness of CCR5-Tropic Human Immunodeficiency Virus Type 1 Isolates of Subtypes B and C

Abstract: Continual human immunodeficiency virus type 1 (HIV-1) evolution and expansion within the human population have led to unequal distribution of HIV-1 group M subtypes. In particular, recent outgrowth of subtype C in southern Africa, India, and China has fueled speculation that subtype C isolates may be more fit in vivo. In this study, nine subtype B and six subtype C HIV-1 isolates were added to peripheral blood mononuclear cell cultures for a complete pairwise competition experiment. All subtype C HIV-1 isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
240
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(260 citation statements)
references
References 78 publications
17
240
1
2
Order By: Relevance
“…This finding is not consistent with the hypothesis that reduced replication fitness in cell culture correlates with reduced transmission efficiency. Of note is that some studies suggested that replication in dendritic cells may be a better predictor of transmission efficiency (50); no differences between the replication of subtype B and C isolates were observed in dendritic cells, consistent with this theory (11). The authors of that study argued that the reduced replication fitness in PBMCs correlates with reduced pathogenicity rather than transmission efficiency (see below).…”
Section: Transmission Efficiencysupporting
confidence: 66%
See 2 more Smart Citations
“…This finding is not consistent with the hypothesis that reduced replication fitness in cell culture correlates with reduced transmission efficiency. Of note is that some studies suggested that replication in dendritic cells may be a better predictor of transmission efficiency (50); no differences between the replication of subtype B and C isolates were observed in dendritic cells, consistent with this theory (11). The authors of that study argued that the reduced replication fitness in PBMCs correlates with reduced pathogenicity rather than transmission efficiency (see below).…”
Section: Transmission Efficiencysupporting
confidence: 66%
“…However, another study demonstrated that subtype C, which is the most common subtype globally, actually has reduced replication fitness compared to subtype B in PBMCs (6,11). This finding is not consistent with the hypothesis that reduced replication fitness in cell culture correlates with reduced transmission efficiency.…”
Section: Transmission Efficiencycontrasting
confidence: 53%
See 1 more Smart Citation
“…1D). In addition to the HIV p24 staining and transmission electron microscopy (TEM), we have recently reported that HIV transcripts can be detected and quantified within crawl-out LCs, further confirming productive infection of these cells (40).…”
Section: R5 Hiv Replicates Within Lcsmentioning
confidence: 97%
“…Whether CCR5 influences initial infection at the level of the LCs, at the level of the epithelial cell (43,44), at early replication steps in lymphoid tissue, or at multiple sites, however, is less clear. The former theories can be described as primary gatekeeper models, whereas the latter process represents a viral fitness model (40).…”
Section: Discussionmentioning
confidence: 99%